2012
DOI: 10.1002/bjs.8714
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing infrahepatic inferior vena cava clamping with low central venous pressure in complex liver resections involving the Pringle manoeuvre

Abstract: NCT01355887 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
62
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 26 publications
0
62
3
Order By: Relevance
“…Bias is likely to have been introduced by variation in surgical skill and perioperative care. However, our results were strengthened by a recent large RCT of 192 patients conducted by Zhu et al 15 These scholars indicated that portal triad clamping combined with infrahepatic IVC clamping is more efficacious in controlling bleeding during complex hepatectomies than portal triad clamping with low CVP.…”
Section: Discussioncontrasting
confidence: 65%
“…Bias is likely to have been introduced by variation in surgical skill and perioperative care. However, our results were strengthened by a recent large RCT of 192 patients conducted by Zhu et al 15 These scholars indicated that portal triad clamping combined with infrahepatic IVC clamping is more efficacious in controlling bleeding during complex hepatectomies than portal triad clamping with low CVP.…”
Section: Discussioncontrasting
confidence: 65%
“…Eight randomized controlled trials (RCTs) met the inclusion criteria with 339 patients with a significantly lower CVP and 342 control patients. Patient demographics and indications for a hepatic resection are displayed in Table . Bias assessment scores for included trials are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In cases of massive backflow from the hepatic veins, the most frequently used procedures were the control of selective hepatic veins (43%) and IVC clamping (40%). Recently, 2 prospective randomized controlled studies proved the efficacy of IVC clamping for reducing blood loss [35,36]. Total vascular exclusion, in which the infra- and suprahepatic IVCs are clamped, has been reported to be an effective procedure to achieve a bloodless liver resection [20,21].…”
Section: Discussionmentioning
confidence: 99%